Mitologi dan Konstruksi Budaya Masyarakat Bubakan Mijen Semarang dalam Tinjauan Roland Barthes - Aziz, Fakhrudin (FIKRAH, 2020)
This article examines the process of meaning construction of mythology which takes its toll on cultural reconstruction in a society. The researcher employed Roland Barthes's Semiotic theory. By this theory, mythology is examined based on the significance of meaning, from denotation to connotation through the operationalization of sign, signifier, and signified. The object of this research is the people of Bubakan Mijen Semarang. The data collection technique includes observation and interview. This study shows that the cultural variants in the Bubakan Mijen Semarang community such as punggahan, pudunan and kabumi are rooted in mythology which emerged and passed down from generation as an ultimate value which is influenced by the factors of ideology, geography, economics, and education. This article signifies the importance of knowing the cultural roots of society through the repositioning of mythology, from historical science to formal science